(untitled) (Biological Sciences - PJSIR, 1996)
Examination of the intestinal tracts (both small and large) of 208 apparently healthy slaughtered Black Bengal goats from different parts of Bangladesh revealed Oesophagostomum columbianum infection in 185(88.94%) cases. In the presence of the parasites, nodular lesions weredetected in thewallof the intestines of 166(79.81%)goats. The mean worm burden (28.66) and the number of nodules (30.88) varied independently. Both worm burden and nodule formation were found to be very much agedependent (p<O.Ol),higherin goats above 18months old, but without any seasonal variations (p>0.05). Sex of the animals had significant bearing on nodule formation, more in male than in female goats (p<0.05). The mucous membrane of the intestines were inflammed, discoloured and covered with mu- cus. Slightly yellow to green coloured nodules of various sizeswere seenon theouter surface of the intestines. There was destruction and desquamation of the villar epithelium due to invasion of parasites. In many cases larval worms were present inside the nodules and destruction of the muscularis mucosa and submucosa was noted. At places, the nodules contained central caseaous mass surrounded by chronic inflammatory cells, mostly lymphocytes and mac- rophages.